Kompetensi Pedagogik Guru TK Ditinjau Dari Tingkat Pendidikan Guru di Gugus I Anggrek Kecamatan Karanganyar Kabupaten Karanganyar Tahun 2015/2016 - Pratiwi, Furi; , Drs. Ilham Sunaryo, M.Pd AUD (2015)
Each kindergarten teacher in Cluster I Orchid Subdistrict Karanganyar Karanganyar Regency of 63 members of the teachers and pedagogic competencies varied education level. Various levels of education ranging from SMA/SMK to the College and experience started became a teacher ever led to the competence of the teacher owned pedagogy. The presence of the background problems, researchers want to conduct research purpose are: (1) To find out the pedagogic competencies kindergarten teachers of the last level of education for teachers in the cluster I Orchid Subdistrict Karanganyar, Karanganyar Regency; (2) To find out if there is a connection-level teacher education with kindergarten teacher in pedagogic competence Cluster I Orchid Subdistrict Karanganyar, Karanganyar Regency. he research method used i.e. descriptive quantitative research with this type of study korelasional. This research hypothesis test using correlation analysis technique Product Moment by using the help of SPPS for windows application program 17.00. Test results obtained by the number of respondents 0.714 rxy 32 people on the significance level 0.05, rtable 0.349. Based on these calculations show that rhitung > rtable or on the significance of 0.05. When rhitung > rtabel then Ho denied so that the hypothesis test of competence of pedagogic kindergarten teacher (questioner) with the level of teacher education (documentation) has to do. Thus it can be concluded that there is a relationship between the pedagogic competencies kindergarten teachers with the educational level of teachers in the cluster I Orchids, Karanganyar, Karanganyar Regency 2015/2016.